KAJIAN PERAN DAN MOTIF : PARTAI MAHASISWA INDONESIA (PMI) DALAM PERPSEPKTIF FILANTROPI - Alhadar, Sofyan; Katili, Andi Yusuf; Rachman, Ellys; Sahi, Yayan; Laudengi, Umriani T (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2022)
The existence of a multi-party system embraced by the Indonesian nation, gives legitimacy to individuals and groups with open space has the right to establish political parties. This is in line with the principle of democratic rights in accordance with the constitution of the Indonesian nation where there is a guarantee of freedom of expression through a forum for organizations or political parties. This study aims to describe the motives for the establishment of the Indonesian student party, using a philanthropic approach. Where philanthropy is a method of measuring human behavior that has great expectations and realities. The methods used in this research are qualitative and case studies use prime and secondary data analysis techniques. As a result of this research, the establishment of the Indonesian student party in the inauguration on the basis of expectations and incompatible realities in the government system is a driving factor for the formation of the party (PMI). In addition, the presence of this party was also mediated by the growth initiated by the group that wanted change.